Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In solving an eigenvalue problem, I've come to following equation ($\lambda=1$): $$\begin{pmatrix} \cos(\theta) & \sin(\theta) \\ \sin(\theta) & -\cos(\theta) \end{pmatrix}\begin{pmatrix} a \\ b \end{pmatrix}=\begin{pmatrix} a \\ b \end{pmatrix}$$ Now, the solution says, "This matrix equation can be reduced to a single equation": $$a \sin(\frac{1}{2}\theta)=b\cos(\frac{1}{2}\theta)$$ I've been rotating trigonometric formulas to get to this, but I simply can't find the way. Could you help me with this, or at least give me a hint?

share|cite|improve this question
up vote 5 down vote accepted

Since the matrix has the eigenvalue 1, it's enough to consider only the first row. Rearrange to get $(1-\cos(\theta))a = \sin(\theta)b$ which if you expand by the right formulae, give you $2(\sin(\theta/2)^2)a = 2\sin(\theta/2)\cos(\theta/2)b$. Now, if your matrix has to be non-identity, then this will give you the equation want.

share|cite|improve this answer

$$\begin{pmatrix} \cos(\theta) & \sin(\theta) \\ \sin\theta & -\cos\theta \end{pmatrix}\begin{pmatrix} a \\ b \end{pmatrix}\\=\begin{pmatrix} a\cos\theta+b\sin\theta \\ a\sin\theta-b\cos\theta \end{pmatrix}=\begin{pmatrix} a \\ b \end{pmatrix}$$ Which gives us the following system of equations: $$a\cos\theta+b\sin\theta=a\tag{1}$$ $$a\sin\theta-b\cos\theta=b\tag{2}$$

So from $(1)$ you have:


$$2b\sin(\frac \theta{2})\cos(\frac \theta{2})=a(2\sin^2(\frac \theta{2}))$$ $$b\cos(\frac \theta{2})=a\sin(\frac \theta{2})$$

share|cite|improve this answer

The matrix system corresponds to the following system of equations \begin{equation} \cos(\theta)\,a + \sin(\theta) b = a \,, \\ \sin(\theta)\,a - \cos(\theta) b = b \, \end{equation} Multiplying the first equation by $\sin(\theta)$ and the second by -$\cos(\theta)$ gives \begin{equation} \sin(\theta)\,\cos(\theta)\,a + \sin(\theta)^2 b = a\,, \\ -\sin(\theta) \cos(\theta) \,a + \cos(\theta)^2 b = -b \, \end{equation}

Add the two equations, and the simplify the resulting equation, you get

$$ b( 1+\cos(\theta) ) = a\,\sin(\theta) $$

Using the identity $ \cos(\theta) = 2\cos(\theta /2)^2 -1 $ and $\sin(\theta) = 2 \sin(\theta /2) \cos(\theta /2) $ in the above equation yields

$$ 2 b \cos(\theta /2)^2 = 2 a \sin( \theta /2 ) \cos( \theta /2 )$$

Dividing both sides of the equation by $\cos(\theta /2)$ gives the result

$$ b \cos(\theta /2) = a \sin( \theta /2 ) $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.